2021
DOI: 10.1113/jp280569
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maternal position, in late gestation pregnancy, on placental blood flow and oxygenation: an MRI study

Abstract: Key points Maternal supine sleep position in late pregnancy is associated with an increased risk of stillbirth. Maternal supine position in late pregnancy reduces maternal cardiac output and uterine blood flow. Using MRI, this study shows that compared to the left lateral position, maternal supine position in late pregnancy is associated with reduced utero‐placental blood flow and oxygen transfer across the placenta with an average 6.2% reduction in oxygen delivery to the fetus and an average 11% reduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 63 publications
5
37
0
Order By: Relevance
“…Depending on the fetal condition and gestational age, an emergent Caesarean delivery may be indicated 1. When EC is selected, potential fetal risks should be reduced by using abdominal shielding,23 minimizing the use of contrast as far as able,24 and proper positioning of the mother during and after the procedure to maximize venous return and placental blood flow 25. No prior studies have compared EC and NC for the treatment of ruptured IA during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the fetal condition and gestational age, an emergent Caesarean delivery may be indicated 1. When EC is selected, potential fetal risks should be reduced by using abdominal shielding,23 minimizing the use of contrast as far as able,24 and proper positioning of the mother during and after the procedure to maximize venous return and placental blood flow 25. No prior studies have compared EC and NC for the treatment of ruptured IA during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, functional MRI techniques have demonstrated that lying supine, as compared with left lateral, resulted in a 24% reduction in total internal iliac arterial blood flow to the uterus, with a 6.2% reduction in oxygen movement across the placenta (Couper et al . 2021). During supine wakefulness, surrogate markers of fetal hypoxia on Doppler flow measurements have been reported (Khatib et al .…”
Section: Discussionmentioning
confidence: 99%
“…MRI is increasingly used to image the placental circulation. The DECIDE multi-compartment model separates fetal and maternal flow characteristics of the placenta allowing measurement of the relative proportions of vascular spaces [6,7]. When applied in early-onset FGR, it identified reduced feto-placental blood oxygen saturation, where the degree of abnormality correlated with disease severity defined by ultrasound fetal and maternal arterial Doppler findings [8].…”
Section: Introductionmentioning
confidence: 99%